Modelagem para mensuração de desempenho competitivo das empresas do setor vitivinícola na região Sul do Brasil - Cattelan, Verônica Dalmolin (2015)
Use of Performance Measurement Systems through multi-criteria analysis to support the decision is constituted as an important tool that can support the diagnosis of competitiveness of organizations. Since the approach is intertwined with the business results and more specifically to the competition, this work focuses on measuring the performance of companies in the wine industry in southern Brazil, from business and industry dimensions. For this we opted for a qualitative and quantitative research, exploratory and descriptive, conducted through a multi case study. From the development of modeling and application in the wine sector in the region under study, it became possible to verify the criteria and critical success factors in the competitive landscape, that through multi-criteria analysis and use of performance indicators enabled the identification of prioritizing factors and the distinction regarding organizational performance in the context of the evaluated dimensions. The overall picture shows that only one of the companies surveyed can be considered fully competitive, confirming the strength of the pressures on the sector and the absence of strategies that allow companies a representative expansion.